Modeling a human hepatocellular carcinoma subset in mice through coexpression of met and point‐mutant β‐catenin. Issue 5 (28th May 2016) - Tao, Junyan; Xu, Emily; Zhao, Yifei; Singh, Sucha; Li, Xiaolei; Couchy, Gabrielle; Chen, Xin; Zucman‐Rossi, Jessica; Chikina, Maria; Monga, Satdarshan P.S.
Abstract : Hepatocellular cancer (HCC) remains a significant therapeutic challenge due to its poorly understood molecular basis. In the current study, we investigated two independent cohorts of 249 and 194 HCC cases for any combinatorial molecular aberrations. Specifically we assessed for simultaneous HMET expression or hMet activation and catenin β1 gene (CTNNB1) mutations to address any concomitant Met and Wnt signaling. To investigate cooperation in tumorigenesis, we coexpressed hMet and β‐catenin point mutants (S33Y or S45Y) in hepatocytes using sleeping beauty transposon/transposase and hydrodynamic tail vein injection and characterized tumors for growth, signaling, gene signatures, and similarity to human HCC. Missense mutations in exon 3 of CTNNB1 were identified in subsets of HCC patients. Irrespective of amino acid affected, all exon 3 mutations induced similar changes in gene expression. Concomitant HMET overexpression or hMet activation and CTNNB1 mutations were evident in 9%‐12.5% of HCCs. Coexpression of hMet and mutant‐β‐catenin led to notable HCC in mice. Tumors showed active Wnt and hMet signaling with evidence of glutamine synthetase and cyclin D1 positivity and mitogen‐activated protein kinase/extracellular signal‐regulated kinase, AKT/Ras/mammalian target of rapamycin activation. Introduction of dominant‐negative T‐cell factor 4 prevented tumorigenesis. The gene expression of mouse tumors in hMet‐mutant β‐catenin showed high correlation, with subsets of human HCC displaying concomitant hMet activation signature and CTNNB1 mutations. Conclusion : We have identified cooperation of hMet and β‐catenin activation in a subset of HCC patients and modeled this human disease in mice with a significant transcriptomic intersection; this model will provide novel insight into the biology of this tumor and allow us to evaluate novel therapies as a step toward precision medicine. (Hepatology 2016;64:1587‐1605)